2014
DOI: 10.1002/2013jd021355
|View full text |Cite
|
Sign up to set email alerts
|

View angle dependence of MODIS liquid water path retrievals in warm oceanic clouds

Abstract: We investigated the view angle dependence of domain mean Moderate Resolution Imaging Spectroradiometer (MODIS) liquid water path (LWP) and that of corresponding cloud optical thickness, effective radius, and liquid cloud fraction as proxy for plane-parallel retrieval biases. Independent Advanced Microwave Scanning Radiometer-EOS LWP was used to corroborate that the observed variations with sun-view geometry were not severely affected by seasonal/latitudinal changes in cloud properties. Microwave retrievals sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
40
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 63 publications
5
40
0
Order By: Relevance
“…It is shown that, besides such characteristics as the averaging scale, instrument/orbit properties, etc., the results of retrieving COD and REF depend strongly on sun-view geometry and cloud heterogeneity. This is confirmed by the simulation results in 2D and 3D cloud models [38,[40][41][42][43][44][45][46].…”
Section: Introductionsupporting
confidence: 80%
“…It is shown that, besides such characteristics as the averaging scale, instrument/orbit properties, etc., the results of retrieving COD and REF depend strongly on sun-view geometry and cloud heterogeneity. This is confirmed by the simulation results in 2D and 3D cloud models [38,[40][41][42][43][44][45][46].…”
Section: Introductionsupporting
confidence: 80%
“…CPR data were used for rain detection, whereas CALIOP cloud top temperature data served to identify warm cloud conditions. The adiabatic assumption (e.g., Greenwald, ) was applied to the MODIS 0.86‐μm optical thickness/3.7‐μm effective radius all‐sky CWP products for solar zenith angles ≤45°, which represents the most conservative threshold when noticeable biases begin to occur in these products (Greenwald, ; Grosvenor & Wood, ; Horváth et al, ; Lebsock & Su, ). The 3.7‐μm effective radius data were chosen because they are less impacted by drizzle (Lebsock et al, ) and cloud inhomogeneities (e.g., Painemal, Minnis, & Sun‐Mack, ; Zhang et al, ) than other wavelengths.…”
Section: Methodsmentioning
confidence: 99%
“…A variety of observational case studies and process studies were also published using similar approaches for deriving CDNC (Boers et al, 2006;George and Wood, 2010;Painemal and Zuidema, 2010;Rausch et al, 2010;. Various authors have addressed shortcomings and issues related to CDNC climatologies (Merk et al, 2016;Grosvenor and Wood, 2014) as well as issues related to the cloud retrievals underlying the CDNC climatologies (Zhang and Platnick, 2011;Nakajima et al, 2010;Maddux et al, 2010;Horvath et al, 2014). Painemal and Zuidema (2011) validate MODIS-derived CDNC against in situ observations taken in the South Pacific during VOCALS-Rex (Wood et al, 2011).…”
Section: Introductionmentioning
confidence: 99%